Influence of short-term inertial training on swimming performance in young swimmers - Naczk, M.; Lopacinski, A.; Brzenczek-Owczarzak, W.; Arlet, J.; Naczk, A.; Adach, Z. (European Journal of Sport Science, 2017)
The aim of this study was to evaluate the influence of dry-land inertial training (IT) on muscle force, muscle power, and swimming performance. Fourteen young, national-level, competitive swimmers were randomly divided into IT and control (C) groups. The experiment lasted four weeks, during which time both groups underwent their regular swimming training. In addition, the IT group underwent IT using the Inertial Training Measurement System (ITMS) three times per week. The muscle groups involved during the upsweep phase of the arm stroke in front crawl and butterfly stroke were trained. Before and after training, muscle force and power were measured under IT conditions. Simultaneously with the biomechanical measurements on the ITMS, the electrical activity of the triceps brachii was registered. After four weeks of training, a 12.8% increase in the muscle force and 14.2% increase in the muscle power (p < .05) were noted in the IT group. Moreover, electromyography amplitude of triceps brachii recorded during strength measurements increased by 22.7% in the IT group. Moreover, swimming velocity in the 100 m butterfly and 50 m freestyle improved significantly following the four weeks of dry-land IT (-1.86% and -0.76%, respectively). Changes in the C group were trivial. Moreover, values of force and power registered during the ITMS test correlated negatively with the 100 m butterfly and 50 m freestyle swimming times (r value ranged from -.80 to -.91). These results suggest that IT can be useful in swimming practice.